Chloroplast Control Mechanisms by Molecular Electronic Device - Yuri Shapovalov; Lyazzat Gumarova (Proceedings)
The aim of this research is to study the light phase of photosynthesis based on X-ray diffraction data from photosystems I and II (PS-I and PS-II), as well as the molecular structures of solar energy conversion and electron flow control systems [...]